A source powder pre-sintering method for reducing oxygen impurity content in aluminum nitride crystals
Through the three-stage heating-removing oxygen impurities and high-low temperature cycle sintering method, the problem of difficulty in reducing oxygen impurities in the growth of aluminum nitride single crystals by PVT method is solved, and the preparation of high-quality aluminum nitride single crystals is achieved.
Patent Information
- Application Number
- CN202111485440.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-12-07
AI Technical Summary
During the PVT method of growing single crystals of aluminum nitride, it is difficult to effectively reduce the oxygen impurities in the aluminum nitride source powder, resulting in a decrease in single crystal ratio, a decrease in crystal size and an increase in dislocation, affecting its ultraviolet photoelectric properties.
The presintering method of three-stage heating-raising oxygen impurities is adopted, including three stages: low temperature, medium temperature and high temperature. The water, surface oxygen impurities and internal oxygen impurities in the source powder are removed respectively, and the source powder particles are added through high and low temperature cycle sintering method. The particle size reduces the specific surface area, thereby reducing the possibility of secondary adsorption of oxygen impurities.
The oxygen impurity content in the aluminum nitride single crystal is effectively reduced, the quality and performance of the single crystal is improved, and the preparation of high-quality aluminum nitride single crystal is realized.
Smart Images

Figure CN116239088B_ABST
Abstract
Description
Technical Field
[0001] This patent relates to semiconductor manufacturing processes, growth technology for controlling oxygen impurity content in aluminum nitride crystals, and specifically to a method for pre-sintering aluminum nitride source powder used for aluminum nitride crystal growth. Background Art
[0002] Aluminum nitride single crystal substrates have excellent properties such as wide band gap, high thermal conductivity, small lattice and thermal mismatch with nitrides, and have attracted much attention due to their wide applications in military and civilian fields such as lasers, sensors, LEDs and power electronic devices. Therefore, the preparation of large-size, high-quality aluminum nitride single crystal substrates has always been a global research hotspot, and physical vapor transport (PVT) is considered to be the most suitable method to date because of its high growth rate and easy control of dislocation density. However, the industrial application of aluminum nitride single crystal substrates is still very difficult, among which impurity and purity control is an important factor. In the process of PVT growth of aluminum nitride crystals, due to the presence of crucibles, heating systems and source powders, especially the large amount of oxygen adsorbed in aluminum nitride (AlN) source powder, it is difficult to reduce the oxygen impurity content in the subsequent single crystal growth. Oxygen impurities will lead to a decrease in the single crystal rate during growth, a reduction in crystal size, dislocations, etc., and further affect the ultraviolet optoelectronic properties of AlN crystals, thereby affecting the performance of various ultraviolet and power devices prepared as substrates. Therefore, in the process of PVT growth of aluminum nitride crystals, the control of oxygen impurities has received widespread attention.
[0003] After long-term research, it was found that the oxygen impurities in aluminum nitride crystals grown by the PVT method mainly come from the AlN source powder. Therefore, the source powder must be pre-sintered to remove the main oxygen impurities before single crystal growth. At present, the conventional AlN source powder pre-sintering technology mainly uses the method of segmented control of sintering temperature to remove oxygen impurities: such as low-temperature sintering to remove H2O molecules adsorbed on the surface of the source powder, medium-temperature sintering to remove oxygen atoms adsorbed on the surface of the source powder, and high-temperature sintering to remove oxygen atoms inside the source powder. This method can effectively reduce the oxygen content in the subsequent PVT-grown AlN crystal from 10 19 cm -3 Reduced to 0.6-2x10 18 cm -3 However, it is very difficult to further reduce the oxygen impurity content using this method. Analysis shows that the main problem with the traditional segmented sintering technology is that the particle size of the source powder does not increase significantly after pre-sintering. After the pre-sintering is completed, when the crucible is opened and the seed crystal is placed, the source powder will re-absorb oxygen, thereby reintroducing oxygen impurities.
[0004] It can be seen that there are many problems with the source powder pre-sintering technology used for PVT growth of aluminum nitride single crystals, so there is an urgent need for a new method to reduce the re-oxidation of the source powder after pre-sintering. Summary of the invention
[0005] In order to overcome the shortcomings of the above-mentioned existing aluminum nitride source powder pre-sintering technology, the present invention proposes a new aluminum nitride source powder pre-sintering method, which can effectively reduce the oxygen impurity content in the subsequently grown aluminum nitride single crystal, and the process is simple, which is conducive to the low-cost preparation of high-quality aluminum nitride single crystals.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for pre-sintering aluminum nitride source powder, characterized in that it comprises the following steps:
[0008] 1) Select high-purity AlN powder as source powder and put the source powder into a crucible;
[0009] 2) Place the crucible in a heating furnace, evacuate it, and then fill it with a mixed gas of argon Ar and nitrogen N2, with nitrogen serving as the source gas to protect the source powder from decomposition at high temperatures;
[0010] 3) Three-stage heating to remove oxygen impurities, heating rate 50-500℃ / h, specific steps include:
[0011] 3-1) Raise the temperature to 300-900°C and maintain for 5-15 hours to remove water from the source powder;
[0012] 3-2) Raise the temperature to 1200-1500°C and maintain for 10-30 hours to remove oxygen impurities on the surface of the source powder;
[0013] 3-3) Raise the temperature to 1850-2000°C and maintain for 10-30 hours to remove oxygen impurities in the source powder;
[0014] 4) Increase the particle size of the source powder and reduce the total specific surface area of the source powder;
[0015] 5) Lower the temperature to room temperature and take out the pre-sintered source powder.
[0016] Wherein, in step 1), the purity of AlN powder is ≥99.99%, and the particle size range is 1-10 microns.
[0017] Furthermore, the crucible material in step 1) includes but is not limited to a high purity tungsten W crucible, a high purity graphite / tantalum carbide (C / TaC) composite crucible, a high purity tantalum / tantalum carbide (Ta / TaC) composite crucible and a tantalum carbide TaC ceramic crucible.
[0018] Furthermore, after the source powder is loaded into the crucible in step 1), the crucible is vibrated to increase the filling density of the source powder.
[0019] Furthermore, the heating furnace in step 2) includes but is not limited to a high-purity tungsten resistance heating furnace, a high-purity graphite induction heating furnace and a high-purity tungsten induction heating furnace, and the selection of crucible materials is mainly coordinated with different heating methods: high-purity tungsten crucible is mainly suitable for high-purity tungsten induction heating furnace and high-purity tungsten induction heating furnace; high-purity graphite / tantalum carbide (C / TaC) composite crucible is mainly suitable for high-purity graphite induction heating furnace; high-purity tantalum / tantalum carbide (Ta / TaC) composite crucible and tantalum carbide TaC ceramic crucible can be used in all three heating furnaces.
[0020] Furthermore, in step 2), the volume ratio of argon Ar and nitrogen N2 is Ar:N2=0.5-3:1.
[0021] Further, in step 2), the vacuum is evacuated to 10 -3 -10 -4 Pa, and then filled with a mixed gas of argon Ar and nitrogen N2, and the pressure was maintained at 600-900Torr.
[0022] Furthermore, step 4) adopts a high and low temperature cycle sintering method, specifically: lower the temperature to 1500-1700°C, maintain for 1-10 hours, then increase the temperature to 1850-2000°C, maintain for 5-15 hours, repeat cooling and heating 2-5 times, wherein the heating and cooling rate is 50-1200°C / h.
[0023] Compared with the prior art, the present invention has the following obvious technical effects:
[0024] The present invention provides a new method for pre-sintering source powder used for growing aluminum nitride crystals. The method first removes oxygen impurities from the aluminum nitride source powder in three stages, and then reduces the specific surface area of the source powder by increasing the particle size of the source powder, thereby reducing the ability of the source powder to absorb oxygen elements secondary to the source powder. The source powder obtained by the present invention is used for subsequent PVT method growth of aluminum nitride single crystals, which can reduce the oxygen content in the aluminum nitride single crystal. SIMS measurement found that the total specific surface area of the AlN source powder after pre-sintering increased from 0.36m 2 / g dropped to 0.13m 2 / g, the oxygen impurity content of the subsequently grown AlN wafer increases from 6x10 17 cm -3 Reduce to 1x10 17 cm -3 The present invention can significantly reduce the oxygen impurity content in the wafer, which is beneficial to the preparation of high-quality aluminum nitride single crystals. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a process flow diagram of a specific embodiment of the present invention;
[0026] Figure 2This is a scanning electron microscope image of source powder particles after the three-stage deoxidation and impurity removal process in the first specific embodiment of the present invention. The particle size of the source powder is about 10 microns;
[0027] Figure 3 This is a scanning electron microscope image of the source powder particles after pre-sintering in the first specific embodiment of the present invention. The particle size of the source powder is about 50 microns. DETAILED DESCRIPTION
[0028] The present invention will be further described below by way of embodiments in conjunction with the accompanying drawings, but the scope of the present invention is not limited in any way.
[0029] Embodiment 1:
[0030] refer to Figure 1 As shown, the patented process of the present invention includes:
[0031] 1) Select high-purity AlN powder as source powder, AlN powder purity ≥ 99.99%, particle size = 1-10 microns. Put the aluminum nitride source powder into a tantalum carbide crucible, increase the filling density of the aluminum nitride source powder by vibration, and cover the tantalum carbide crucible with a lid.
[0032] 2) Place the tantalum carbide crucible in a high purity tungsten resistance heating PVT furnace and evacuate to 10 -4 Pa, and maintained for 4 hours to fully remove the large amount of air adsorbed in the reaction chamber and source powder. Then fill in a mixed gas of argon Ar and nitrogen N2, Ar:N2=1:2, and fill until the pressure is maintained at 800Torr. Nitrogen is used as the source gas to protect the source powder from decomposition at high temperature;
[0033] 3) Three-stage deoxidation and impurity removal process:
[0034] Low temperature dehydration: slowly increase the temperature to 800℃ at a heating rate of 200℃ / h and maintain for 8h to allow the low temperature dehydration process to proceed fully;
[0035] Medium temperature surface deoxidation: slowly increase the temperature to 1300℃ at a heating rate of 200℃ / h and maintain for 10h to remove oxygen impurities on the surface of the source powder;
[0036] High temperature internal deoxidation: slowly increase the temperature to 1850℃ at a heating rate of 200℃ / h and maintain for 16h to remove oxygen impurities inside the source powder; the particle size of the source powder particles after three-stage deoxidation is about 10 microns, such as Figure 2 shown.
[0037] 4) High and low temperature cycle sintering method, increase the particle size of the source powder and reduce the total specific surface area of the source powder:
[0038] After the high-temperature internal deoxidation process is completed, the temperature is lowered to 1600°C and maintained for 10 hours, then raised to 1850°C and maintained for 10 hours, with a heating and cooling rate of 300°C / h, and the cooling and heating are repeated 4 times. The phase change process in the high and low temperature cycle is used to promote the increase of the particle size every time the temperature drops. After 4 cycles of cooling, the particle size of AlN particles increases from less than 10 microns to 50 microns. Figure 3 shown.
[0039] 5) Lower the temperature to room temperature and take out the sintered source powder. The particle size of the pre-sintered AlN particles is about 50 microns, and the total specific surface area of the pre-sintered source powder is 0.36m 2 / g dropped to 0.13m 2 / g, the secondary adsorption of oxygen impurities in the source powder after pre-sintering is reduced, which is beneficial to the subsequent PVT growth of aluminum nitride single crystals.
[0040] Embodiment 2:
[0041] The process steps of the present invention include:
[0042] 1) Select high-purity AlN powder as source powder, AlN powder purity ≥ 99.99%, particle size = 1-10 microns. Put the aluminum nitride source powder into a tungsten crucible, increase the filling density of the aluminum nitride source powder by vibration, and cover the tungsten crucible.
[0043] 2) Place the tungsten crucible in a high purity tungsten resistance heating PVT furnace and evacuate to 10 -3 Pa, and maintained for 2 hours to fully remove the large amount of air adsorbed in the reaction chamber and source powder. Then fill in a mixed gas of argon Ar and nitrogen N2, Ar: N2 = 1: 1, and fill until the pressure is maintained at 700 Torr. Nitrogen is used as the source gas to protect the source powder from decomposition at high temperature;
[0044] 3) Three-stage deoxidation and impurity removal process:
[0045] Low-temperature dehydration: slowly increase the temperature to 600°C at a heating rate of 200°C / h and maintain for 5 hours to allow the low-temperature dehydration process to proceed fully.
[0046] Medium-temperature surface deoxidation: slowly increase the temperature to 1400°C at a heating rate of 200°C / h and maintain for 15 hours to remove oxygen impurities on the surface of the source powder.
[0047] High-temperature internal deoxidation: slowly increase the temperature to 1900°C at a heating rate of 200°C / h and maintain for 15 hours to remove oxygen impurities inside the source powder.
[0048] 4) High and low temperature cycle sintering method, increase the particle size of the source powder and reduce the total specific surface area of the source powder:
[0049] After the high-temperature internal deoxidation process is completed, the temperature is lowered to 1550°C and maintained for 2 hours, then raised to 1900°C and maintained for 5 hours, with a heating and cooling rate of 200°C / h, and the temperature is repeated for 3 times. The phase change process in the high and low temperature cycle is used to promote the increase of the particle size every time the temperature drops. After 3 cycles of cooling, the particle size of AlN particles can be increased from less than 10 microns to 25 microns.
[0050] 5) Lower the temperature to room temperature and take out the sintered source powder. The particle size of the pre-sintered AlN particles is about 25 microns, and the total specific surface area of the pre-sintered source powder is 0.36m 2 / g dropped to 0.27m 2 / g, the secondary adsorbed oxygen impurities are reduced, which is beneficial to the subsequent PVT growth of aluminum nitride single crystals.
[0051] It should be noted that the purpose of publishing the embodiments is to help further understand the present invention, but those skilled in the art can understand that various substitutions and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the present invention should not be limited to the contents disclosed in the embodiments, and the scope of protection claimed by the present invention shall be subject to the scope defined in the claims.
Claims
1. A method for pre-sintering aluminum nitride source powder, characterized in that: The steps include: 1) Select high-purity AlN powder as source powder, put the source powder into a crucible, and cover the crucible with a lid; 2) Place the crucible in a heating furnace, evacuate it, and then fill it with a mixed gas of argon Ar and nitrogen N2, with nitrogen serving as the source gas to protect the source powder from decomposition at high temperatures; 3) Three-stage heating to remove oxygen impurities, the specific steps include: 3-1) Raise the temperature to 300-900°C and maintain for 5-15 hours to remove water from the source powder; 3-2) Raise the temperature to 1200-1500°C and maintain for 10-30 hours to remove oxygen impurities on the surface of the source powder; 3-3) Raise the temperature to 1850-2000°C and maintain for 10-30 hours to remove oxygen impurities in the source powder; 4) Increase the particle size of the source powder and reduce the total specific surface area of the source powder. The specific steps are: lower the temperature to 1500-1700°C, maintain for 1-10 hours, then increase the temperature to 1850-2000°C, maintain for 5-15 hours, and repeat the temperature reduction and temperature increase 2-5 times; 5) Lower the temperature to room temperature and take out the pre-sintered source powder.
2. The aluminum nitride source powder pre-sintering method according to claim 1, characterized in that: In step 1), the purity of AlN powder is ≥99.99%, and the particle size range is 1-10 microns.
3. The aluminum nitride source powder pre-sintering method according to claim 1, characterized in that: The crucible material in step 1) is selected from a high-purity tungsten W crucible, a high-purity graphite / tantalum carbide composite crucible, a high-purity tantalum / tantalum carbide composite crucible or a tantalum carbide TaC ceramic crucible.
4. The aluminum nitride source powder pre-sintering method according to claim 1, characterized in that: After the source powder is loaded into the crucible in step 1), the crucible is vibrated to increase the filling density of the source powder.
5. The aluminum nitride source powder pre-sintering method according to claim 3, characterized in that: In step 2), the heating furnace is selected from a high-purity tungsten resistance heating furnace, a high-purity graphite induction heating furnace or a high-purity tungsten induction heating furnace, wherein: the high-purity tungsten crucible is suitable for the high-purity tungsten induction heating furnace and the high-purity tungsten induction heating furnace; the high-purity graphite / tantalum carbide composite crucible is suitable for the high-purity graphite induction heating furnace; the high-purity tantalum / tantalum carbide composite crucible and the tantalum carbide TaC ceramic crucible are suitable for all three heating furnaces.
6. The aluminum nitride source powder pre-sintering method according to claim 1, characterized in that: In step 2), the volume ratio of argon Ar and nitrogen N2 is Ar:N2=0.5-3:
1.
7. The aluminum nitride source powder pre-sintering method according to claim 1, characterized in that: Step 2) Vacuum to 10 -3 -10 -4 Pa, and then filled with a mixed gas of argon Ar and nitrogen N2, and the pressure was maintained at 600-900Torr.
8. The aluminum nitride source powder pre-sintering method according to claim 1, characterized in that: In step 3), the heating rate is 50-500°C / h.
9. The aluminum nitride source powder pre-sintering method according to claim 1, characterized in that: The heating and cooling rate is 50-1200℃ / h.
Citation Information
Patent Citations
High temperature sintering purifying method used for aluminium nitride
CN108275664A
Raw material pretreatment method for high-quality aluminum nitride crystal growth
CN109576783A